Analysis of the bearing behaviour of a screw-pile foundation in silt soil. Issue 4 (10th February 2019) - Jiang, Pengcheng; Xu, Wang; Zhang, Yanjie
Abstract : Screw-pile composite foundations have been widely implemented on multiple high-speed railways in China. Their distinctive design with variable sections makes the bearing behaviour of screw piles far more complex than that of common smooth piles. The bearing behaviour of a screw-pile composite foundation was analysed in silt soil on a national key construction project. A comparative analysis of the bearing characteristics of composite foundations of smooth piles and screw piles was performed through model tests. The results showed that, in a single-pile composite foundation and with the same pile diameter and length, the ultimate bearing capacity of the screw pile was 67% higher than that of the smooth pile. The smooth pile showed an area of negative frictional resistance at the top of the composite foundation. The screw pile had a negative friction area below the junction of the smooth section and the screw section in the screw-pile composite foundation.